Polymer nanocarriers for targeted local delivery of agents in treating brain tumors. (12th February 2023) - Josowitz, Alexander D; Bindra, Ranjit S; Saltzman, W Mark
Abstract: Glioblastoma (GBM), the deadliest brain cancer, presents a multitude of challenges to the development of new therapies. The standard of care has only changed marginally in the past 17 years, and few new chemotherapies have emerged to supplant or effectively combine with temozolomide. Concurrently, new technologies and techniques are being investigated to overcome the pharmacokinetic challenges associated with brain delivery, such as the blood brain barrier (BBB), tissue penetration, diffusion, and clearance in order to allow for potent agents to successful engage in tumor killing. Alternative delivery modalities such as focused ultrasound and convection enhanced delivery allow for the local disruption of the BBB, and the latter in particular has shown promise in achieving broad distribution of agents in the brain. Furthermore, the development of polymeric nanocarriers to encapsulate a variety of cargo, including small molecules, proteins, and nucleic acids, have allowed for formulations that protect and control the release of said cargo to extend its half-life. The combination of local delivery and nanocarriers presents an exciting opportunity to address the limitations of current chemotherapies for GBM toward the goal of improving safety and efficacy of treatment. However, much work remains to establish standard criteria for selection and implementation of these modalities before they can be widely implemented in the clinic. Ultimately, engineering principles and nanotechnology have opened the door to a new wave of research that may soon advance the stagnant state of GBM treatment development.